REFERENSI MODEL CareerEDGE SEBAGAI DETERMINAN KESIAPAN KERJA KELAS XI AKUNTANSI SMK NEGERI SE-KABUPATEN BATANG TAHUN PELAJARAN 2015/2016 - Ardiasih, Siska; Setiyani, Rediana (Economic Education Analysis Journal, 2017)
Tujuan penelitian ini adalah untuk mengetahui pengaruh Career Development Learning; Experience; Degree Subject Knowledge, Understanding, & Skills; Generic Skills; Emotional Intelligence terhadap kesiapan kerja Siswa Kelas XI Akuntansi SMK Negeri se-Kabupaten Batang. Subjek penelitian adalah seluruh siswa kelas XI Akuntansi SMK Negeri se-Kabupaten Batang yang berjumlah 136 siswa, sedangkan sampel berjumlah 101 siswa yang ditentukan dengan teknik proportional random sampling. Metode pengumpulan data menggunakan kuesioner dan dokumentasi. Data dianalisis dengan menggunakan analisis deskriptif persentase dan analisis regresi linier berganda. Hasil analisis deskriptif memberikan informasi kesiapan kerja siswa dalam kategori siap; Career Development Learning; Experience; Degree Subject Knowledge, Understanding, & Skills; Generic Skills; dan Emotional Intelligence berada pada kategori baik. Hasil penelitian secara statistik menunjukkn bahwa terdapat pengaruh Career Development Learning; Experience; Degree Subject Knowledge, Understanding, & Skills; Generic Skills; dan Emotional Intelligence terhadap kesiapan kerja sebanyak 83,3 %. Secara parsial pengaruh masing-masing yaitu Career Development Learning sebesar 20,34 %; Experience sebesar 5,90 %; Degree Subject Knowledge, Understanding, & Skills sebesar 7,18 %; Generic Skills sebesar 10,76 %; dan Emotional Intelligence sebesar 14,67 %. Kesimpulan penelitian ini adalah terdapat pengaruh Career Development Learning; Experience; Degree Subject Knowledge, Understanding, & Skills; Generic Skills; Emotional Intelligence terhadap kesiapan kerja Siswa Kelas XI Akuntansi SMK Negeri se-Kabupaten Batang. The purpose of this study was to determine the effect of Career Development Learning; experience; Degree Subject Knowledge, Understanding, & Skills; Generic Skills; and Emotional Intelligence toward Work Readiness of Accounting Students XIth Grade at VHS in Batang. The subject of this study was the whole Accounting Students XIth Grade VHS in Batang that totaling 136 students. The sample was 101 students choosen by proportional random sampling technique. Data collecting was using questionnaires and documentation methods. Data were analyzed using percentage descriptive analysis and multiple linear regression analysis. From the result of descriptive analysis, it could be concluded that the students work readiness was in ready categories; Career Development Learning; Experience; Degree Subject Knowledge, Understanding, & Skills; Generic Skills; and Emotional Intelligence were in good category. The results of statistic analysis indicated that there were significant influence of Career Development Learning; Experience; Degree Subject Knowledge, Understanding, & Skills; Generic Skills; and Emotional Intelligence toward work readiness 83.3%. Partial influence of Career Development Learning 20.34%; Experience 5.90%; Degree Subject Knowledge, Understanding,& Skills 7.18%; Generic Skills to 10.76%; and Emotional Intelligence 14.67%. The conclusion of this study is that there are significant effect of Career Development Learning; experience; Degree Subject Knowledge, Understanding,& Skills; Generic Skills; Emotional Intelligence toward work readiness of Accounting Students XIth Grade in Batang.